Evaluation of psychometric properties of the Persian version of the predicaments questionnaire, exploring social attitudes to suicide - Rafati, Ali; Janani, Leila; Malakouti, Seyed Kazem; Motevalian, Seyed Abbas; Kabiri, Ali; Pasebani, Yeganeh; Shalbafan, Mohammadreza (Frontiers in Public Health, 2023)
Background: Due to the growing prevalence of suicide, assessing people's attitudes toward suicide is necessary. Therefore, this study aimed to examine the psychometric properties of the Persian version of the Predicaments Questionnaire (PQ), measuring social attitudes toward suicide. Methods This psychometrics study evaluated face validity, content validity, temporal stability, internal consistency, and construct validity. First, the questionnaire was translated into Persian by the translate-back-translate method. The Persian version was provided to 10 experts in psychiatry for further revision. Two indicators, CVR and CVI, were calculated to evaluate the content validity. To check the face validity, we prepared a form and gave it to 10 people outside the campus to submit their opinions. Temporal stability was investigated by the test-retest method, reporting Intraclass correlation (ICC). Internal consistency was assessed by reporting Cronbach's alpha and McDonald's Omega coefficients. Construct validity was assessed using the confirmatory factor analysis to determine the number of dimensions of the questionnaire. Results A total of 151 students were enrolled with a mean age of 25 (SD = 0.32). The Persian PQ was valid in terms of content validity and face validity. Furthermore, it was reliable as Cronbach's alpha, McDonald's Omega, and the ICC were 0.94, 0.943, and 0.998, respectively. In addition, the confirmatory factor analysis yielded one dimension. Finally, after reviewing the experts' comments, the final amendments were made, and only question 29 was removed from the final version. Conclusion Consequently, the Persian version of the PQ is acceptable in terms of content validity, face validity, temporal stability, and internal consistency.